Smart prosthetic hand / Muhammad Azri Abdul Basir, Muhammad Farid Abdul Khalid and Muhammad Aiman Abdul Aziz - Abdul Basir, Muhammad Azri; Abdul Khalid, Muhammad Farid; Abdul Aziz, Muhammad Aiman (2019)
Lifix Sdn Bhd is a company that produces advance prosthesis device regarding to hand limb problems which consist technology involvement that can behave like a real hand. Such technology example is muscle sensor which can detect muscle signal or electromyography (EMG). In definition, electromyography or EMG is a study of muscle electrical signals. Sometimes it is known as myoelectric activity. When a muscle tissue makes some movements, it will produce electrical potential similar to the way nerves do and the name given to these electrical signals is the muscle action potential. Lifix is created based on the agreement among three members who are interested to have a strong market position in Malaysia. Lifix company focusing on rehabilitation technology and trying to reduce the cost for such technology that already existed in markets. With the product, Lifix can help amputee victims around Malaysia peninsular related to loss of hand. This product can mimic several real hand movements and can perform simple tasks such as writing, pointing and do hand symbols.